2009
DOI: 10.1099/ijs.0.009647-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium tibeticum sp. nov., a symbiotic bacterium isolated from Trigonella archiducis-nicolai (Sirj.) Vassilcz.

Abstract: Rhizobium tibeticum sp. nov., a symbiotic bacterium isolated from Trigonella archiducisnicolai (Š irj.) Vassilcz. Isolated from root nodules of Trigonella archiducis-nicolai (Š irj.) Vassilcz. grown in Tibet, China, cells of the bacterial strains CCBAU 85039 T and CCBAU 85027 were Gram-negative, aerobic, motile, non-spore-forming rods that formed colonies that were semi-translucent and opalescent on yeast extract-mannitol agar. In numerical taxonomy, SDS-PAGE analysis of whole-cell proteins and DNA-DNA hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…R. rosettiformans W3 T and R. borbori DN316 T were incubated for 36 h in TSB medium at 28 u C since they have faster growth rates than strain K-38 T . Fatty acids were extracted (Hou et al, 2009) and identified using the standard method of the Microbial Identification System (MIDI) by GC (6850; Agilent) using the database TSBA6 for identification of the peaks. The cellular fatty acid profile of strain K-38 T contained summed feature 8 (comprising C 18 : 1 v7c and/or C 18 : 1 v6c; 57.2 %), C 16 : 0 (13.6 %) and summed feature 2 [comprising C 12 : 0 aldehyde, C 14 : 0 3-OH/iso-C 16 : 1 I and/or unknown equivalent chain length (ECL) 10.928; 11.0 %] as major components.…”
Section: Characteristic 1 2mentioning
confidence: 99%
“…R. rosettiformans W3 T and R. borbori DN316 T were incubated for 36 h in TSB medium at 28 u C since they have faster growth rates than strain K-38 T . Fatty acids were extracted (Hou et al, 2009) and identified using the standard method of the Microbial Identification System (MIDI) by GC (6850; Agilent) using the database TSBA6 for identification of the peaks. The cellular fatty acid profile of strain K-38 T contained summed feature 8 (comprising C 18 : 1 v7c and/or C 18 : 1 v6c; 57.2 %), C 16 : 0 (13.6 %) and summed feature 2 [comprising C 12 : 0 aldehyde, C 14 : 0 3-OH/iso-C 16 : 1 I and/or unknown equivalent chain length (ECL) 10.928; 11.0 %] as major components.…”
Section: Characteristic 1 2mentioning
confidence: 99%
“…viciae (Jordan 1984;Laguerre et al 2003;Mutch et al 2003;Slattery et al 2004;Mutch and M. Mahdhi (*) : A. Fterich : M. Rejili : M. Mars Laboratoire de Biotechnologies Végétales Appliquées à l'Amélioration des Cultures, Université de Gabès, Faculté des Sciences de Gabès, Cité Erriadh Zrig, 6072 Gabès, Tunisia e-mail: mosbahtn@yahoo.fr Young 2004;Moschetti et al 2005). Although, Trigonella plants mainly nodulate with Sinorhizobium meliloti (Roumiantseva et al 2002;You et al 2008), strains belonging to the genera Bradyrhizobium (Pandey et al 2004) and Rhizobium (Wang et al 2006;Hou et al 2009) have also been isolated from two Trigonella species in China. The genus Hedysarum L. comprises about 100 species, of herbaceous legumes, widely distributed in the Mediterranean, temperate Europe, North and South Africa, Asia Minor, Siberia, North America from Arizona into Alaska and the Arctic regions of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The results permitted identification of the strains 246-1 and SLD2 as R. tibeticum. R. tibeticum was isolated from Trigonella archiducis-nicolai root nodules in Tibet and found to nodulate M. sativa under laboratory conditions (Hou et al 2009). Our results are the first to confirm the presence of R. tibeticum in root nodules of M. sativa and provide evidence that it can be its natural host plant.…”
Section: Discussionmentioning
confidence: 99%